2009
DOI: 10.1899/08-104.1
|View full text |Cite
|
Sign up to set email alerts
|

Retention of salmon-derived N and P by bryophytes and microbiota in mesocosm streams

Abstract: Annual migrations of anadromous salmon are an important source of nutrients for many coastal streams. Much of the current research on salmon-derived nutrients has focused on nutrient retention via carcass consumption by mammals, birds, and macroinvertebrates, whereas retention and transfer of nutrients by microbiota has received less attention. Our research objective was to investigate nutrient movement from decomposing salmon tissue into periphyton, bryophytes, leaf-pack microbiota, and amphipods in laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In contrast, Ambrose et al (2004) reported that salmon carcass additions to northern California streams had no effect on periphyton biomass or primary production, possibly because of light limitation. However, Peterson and Matthews (2009) reported higher periphyton biomass and significant uptake of salmon-derived nutrients by periphyton, bryophytes, and decomposing leaves when salmon carcasses were added to laboratory streams. Summarizing work to date, it appears that spawning runs of salmon and other anadromous fish can provide nutrient subsidies and enhance nutrient uptake in stream ecosystems through both direct feeding by consumers on carcasses and bottom-up enhancement of periphyton productivity by nutrients released during carcass decomposition, but the latter mechanism might be confined to those streams in which light levels are high and nutrients are strongly limiting.…”
Section: Role Of Consumers In Stream Nutrient Dynamicsmentioning
confidence: 97%
“…In contrast, Ambrose et al (2004) reported that salmon carcass additions to northern California streams had no effect on periphyton biomass or primary production, possibly because of light limitation. However, Peterson and Matthews (2009) reported higher periphyton biomass and significant uptake of salmon-derived nutrients by periphyton, bryophytes, and decomposing leaves when salmon carcasses were added to laboratory streams. Summarizing work to date, it appears that spawning runs of salmon and other anadromous fish can provide nutrient subsidies and enhance nutrient uptake in stream ecosystems through both direct feeding by consumers on carcasses and bottom-up enhancement of periphyton productivity by nutrients released during carcass decomposition, but the latter mechanism might be confined to those streams in which light levels are high and nutrients are strongly limiting.…”
Section: Role Of Consumers In Stream Nutrient Dynamicsmentioning
confidence: 97%
“…The extent of salmon nutrient retention in a watershed will be influenced by variation in seasonal high discharge events and winter freezing in relation to the spawning period, as well as stream variables such as large wood and pools, which facilitate carcass retention (Cederholm and Peterson 1985, Cederholm et al 1989, Minakawa and Gara 2005. The coincidence of salmon spawning and seasonal leaf-litter input, which may vary across regions, could facilitate salmon nutrient retention (Peterson and Matthews 2009). Previous studies of the persistent ecological effects of salmon nutrients on stream invertebrates have occurred in streams with rainfalldriven hydrology characterized by high fall discharge events and that may not freeze predictably over winter (Minakawa and Gara 2003, Lessard and Merritt 2006, Honea and Gara 2009, Lessard et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This provides a nutrient subsidy that can both directly influence organisms that consume salmon eggs or carcasses (e.g., Bilby et al 1998, Minakawa et al 2002 and indirectly alter ecosystem processes when organisms switch their diets to salmon (Zhang et al 2003). Decomposing carcasses can also elevate dissolved nutrient levels, which may increase primary productivity and improve the nutritional quality of biofilm if nutrients are limited (e.g., Johnston et al 2004, Peterson andMatthews 2009).…”
Section: Introductionmentioning
confidence: 99%